Hyaluronidase Expression and Activity Is Regulated by Pro-Inflammatory Cytokines in Human Airway Epithelial Cells - Monzon, Maria Elena; Manzanares, Dahis; Schmid, Nathalie; Casalino-Matsuda, S. Marina; Forteza, Rosanna M (American journal of respiratory cell and molecular biology, 2008)
Hyaluronan (HA) is present at the apical surface of airway epithelium as a high-molecular-weight polymer. Since HA depolymerization initiates a cascade of events that results in kinin generation and growth factor processing, in the present work we used primary cultures of human bronchial epithelial (HBE) cells grown at the air-liquid interface (ALI) to assess hyaluronidase (Hyal) activity by HA zymography, gene expression by quantitative real-time PCR, and localization by confocal microscopy. Because TNF-alpha and IL-1beta induce Hyals in other cells, we tested their effects on Hyals expression and activity. We found that Hyal-like activity is present in the apical and basolateral secretions from HBE cells where Hyals 1, 2, and 3 are expressed, and that IL-1beta acts synergistically with TNF-alpha to increase gene expression and activity. Confocal microscopy showed that Hyals 1, 2, and 3 were localized intracellularly, while Hyal2 was also expressed at the apical pole associated with the plasma membrane, and in a soluble form on the apical secretions. Tissue sections from normal individuals and from individuals with asthma showed a Hyal distribution pattern similar to that observed on nontreated HBE cells or exposed to cytokines, respectively. In addition, increased expression and activity were observed in tracheal sections and in bronchoalveolar lavage (BAL) obtained from subjects with asthma when compared with normal lung donors and healthy volunteers. Our observations indicate that Hyal 1, 2, and 3 are expressed in airway epithelium and may operate in a coordinated fashion to depolymerize HA during inflammation associated with up-regulation of TNF-alpha and IL-1beta, such as allergen-induced asthmatic responses.